1992
DOI: 10.1038/ng0692-199
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation of a candidate gene for Norrie disease by positional cloning

Abstract: The gene for Norrie disease, an X-linked disorder characterized by progressive atrophy of the eyes, mental disturbances and deafness, has been mapped to chromosome Xp11.4 close to DXS7 and the monoamine oxidase (MAO) genes. By subcloning a YAC with a 640 kilobases (kb) insert which spans the DXS7-MAOB interval we have generated a cosmid contig which extends 250 kb beyond the MAOB gene. With one of these cosmids, microdeletions were detected in several patients with Norrie disease. Screening of cDNA libraries h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
121
0
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(123 citation statements)
references
References 31 publications
0
121
0
2
Order By: Relevance
“…At least 50% of patients have various degrees of mental retardation and psychotic features and one third develop progressive sensorineural deafness, usually in the second decade (Warburg, 1966;Parving and Warburg, 1977). The Norrie Disease Protein (NDP) gene, located on chromosome Xp11.1 (Bleeker-Wagemakers et al, 1985), was identified by two groups (Berger et al, 1992a, Chen et al, 1992. So far, the gene product has an unknown function.…”
Section: Introductionmentioning
confidence: 99%
“…At least 50% of patients have various degrees of mental retardation and psychotic features and one third develop progressive sensorineural deafness, usually in the second decade (Warburg, 1966;Parving and Warburg, 1977). The Norrie Disease Protein (NDP) gene, located on chromosome Xp11.1 (Bleeker-Wagemakers et al, 1985), was identified by two groups (Berger et al, 1992a, Chen et al, 1992. So far, the gene product has an unknown function.…”
Section: Introductionmentioning
confidence: 99%
“…The carboxyl terminus of submaxillary mucin is formed by a 240-residue disulfide-rich domain, which has significant sequence identity with similar domains at the carboxyl terminus of human prepro-von Willebrand factor (3), frog integumentary mucin FIMB.1 (6), and human mucins secreted by different tissues, including MUC2, MUC5AC, 4 MUC5B, 5 and MUC6 6 (5,(7)(8)(9)(10). Moreover, the 11 half-cystines in a 133-residue protein (norrin) 7 associated with Norrie disease in humans (11,12) are conserved in the carboxyl-terminal disulfide-rich domains of human prepro-von Willebrand factor, porcine submaxillary mucin, and several human mucins (13). It has been shown that the disulfide-rich domain of prepro-von Willebrand factor (14), porcine submaxillary mucin (15), and norrin (16) forms interchain disulfide bonds between two polypeptide chains in these molecules.…”
mentioning
confidence: 99%
“…it is not translated). 10 Within exons 2 and 3 there is an open reading frame of 399 bp which encodes a protein chain of 133 amino acids (Fig. 5).…”
Section: Ndp Gene Structure and Protein Productmentioning
confidence: 99%